Influences of stress-aging on the precipitation behavior of δ phase (Ni3Nb) in a nickel-based superalloy - Cheng, Hao; Lin, Y.C.; He, Dao-Guang; Qiu, Yu-Liang; Zhu, Jun-Cheng; Chen, Ming-Song (Materials & design, 2021)
The precipitation behaviors of δ phases (Ni3Nb) in a nickel-based superalloy are investigated by stress-free and stress aging tests. The effects of aging parameters on the distribution features of δ phases are discussed. Also, the evolution of dislocation substructures is analyzed. The results show that the extra stress can accelerate the uniform precipitation of δ phase, and increase the dislocation substructures during stress aging treatment. But, in the stress-free aging process, δ phases easily concentrate around grain boundaries and randomly distribute within grains. During the stress aging, with the increase of extra stress or aging time, δ phase regularly and densely precipitates within grains, because the lattice distortion is affected by the extra stress. In addition, the basket-weave δ phases densely precipitate and mutually intersect to form enclosure spaces. The limited dislocations in the enclosure spaces can enhance the formation of subgrains and make the uniform nucleation of dynamic recrystallization grains. Meanwhile, the basket-weave δ phases caused by the extra stress significantly refine the deformed grains, and the uniform microstructures are obtained. [Display omitted] •Precipitation behaviors of δ phases in a nickel-based superalloy are studied by stress-free and stress aging tests.•The stress aging can induce the uniform precipitation of δ phases and increase dislocation substructures•In stress-free aged alloy, δ phases easily concentrate at grain boundaries and randomly distribute within grains.•In the stress aged alloy, δ phase regularly and densely precipitates within grains due to the lattice distortion.•The basket-weave δ phases densely precipitate and mutually intersect to form enclosure spaces.